The light we carry : overcoming in uncertain times [compact disc, unabridged] - Obama, Michelle, 1964- (Random House Audio, 2022)
Drawing from her experiences as a mother, daughter, spouse, friend, and First Lady, Michelle Obama shares the habits and principles she has developed to adapt to change and overcome obstacles.